Comparison of tissue doppler derived systolic strain between different severities of left ventricular dysfunction in patients having rheumatic severe mitral regurgitation (Journal of Fatima Jinnah Medical University, 2020)
Background: Tissue doppler derived systolic strain detects the subtle changes in left ventricular (LV) function. This new modality can detect LV dysfunction in severe rheumatic mitral regurgitation (MR) at earlier stages. The present study was conducted to compare tissue doppler derived peak systolic strain between patients with different severities of LV dysfunction in rheumatic severe MR and to look for the negative correlation between LV dysfunction and peak systolic strain.Subjects and methods: A descriptive correlational study was conducted from January 2017 to March 2018 at Punjab Institute of Cardiology, Lahore. Fifty healthy controls taken as group-I and 150 asymptomatic patients of rheumatic severe MR were divided into Group-II (with ejection fraction (EF) ≥60% and left ventricular end systolic dimension (LVESD) ≤40mm), Group-III (with EF≥ 60% and LVESD 41-50mm) and Group-IV (with EF
Keywords: Mitral regurgitation; Systolic strain; Tissue doppler